The Morphology of English Dialects : Verb Formation in Non-Standard English - Anderwald, Lieselotte (Cambridge University Press, 2013)
In sum, if we extend natural morphology with the psycholinguistically plausible network model, we can link a model employing sophisticated linguistic terminology with possible low-level neural mechanisms, resulting in a highly empirical framework that has been extensively tested and which makes interesting predictions for infl ectional systems, and which will therefore be employed in the remainder of this book